MUDHARABAH, MUSYARAKAH, AND MURABAHAH AS DETERMINING FACTORS OF PROFITABILITY IN ISLAMIC COMMERCIAL BANKS - Sulistyawati, Ardiani Ika; Septiana, Shella; Santoso, Aprih (STIE Pelita Nusantara Semarang, 2025)
This study aims to analyze and assess the impact of mudharabah, musyarakah, and murabahah financing on the profitability of Islamic Commercial Banks (ICBs) in Indonesia, both individually (partially) and collectively (simultaneously). The research focuses on Islamic Commercial Banks registered with the Financial Services Authority (OJK) during 2019–2021. Using linear regression analysis, a quantitative research approach is employed to investigate the influence of mudharabah, musyarakah, and murabahah financing on profitability. The sampling technique used in this study is purposive sampling. At the same time, the dataset consists of secondary data in the form of quarterly financial reports obtained from the official websites of Islamic Commercial Banks for the 2019–2021 period. The analytical methods applied include multiple regression analysis, classical assumption testing, and hypothesis testing. The findings indicate that the independent variables collectively (simultaneously) influence profitability (measured by Return on Assets/ROA). However, when examined individually (partially), mudharabah financing does not exhibit a significant effect, whereas musyarakah and murabahah financing significantly negatively impact ROA.